Preeclampsia asociada a trastornos de coagulación en neonatos atendidos en el Hospital Belén De Trujillo 2018-2019 - Saldivar De La Borda, José Daniel (2022)
Preeclampsia is a hypertensive disorder of pregnancy that can affect between 4 and 8% of pregnancies, causing repercussions in both mothers and their children. Neonatal manifestations are usually associated with alterations in intrauterine growth and homeostasis in fetal life, during labor, in the neonatal stage or may also occur in the long term. Coagulation disorders in the neonate constitute a diagnostic and therapeutic challenge, since alterations in some of the components of coagulation associated with genetic or acquired risk factors can result in hemorrhagic or thromboembolic emergencies. Reasons for which we pose as a question to determine whether: Is preeclampsia a risk factor for coagulation disorders in neonates attended at Hospital Belén de Trujillo in the period 2018-2019? Aiming to determine and compare the frequency of mothers with preeclampsia in neonates with and without coagulation disorders attended at Hospital Belén de Trujillo during the aforementioned period. In the present study, clinical histories of neonates with coagulation disorders seen in the neonatology service of the Hospital Belén de Trujillo in the period 2018-2019 will be reviewed, and the information will be compiled in a Data Collection Form developed for the present study.